Spatio‑temporal dynamics of rainfall erosivity due to climate change in Cameron Highlands, Malaysia - Nasidi, Nuraddeen Mukhtar; Wayayok, Aimrun; Abdullah, Ahmad Fikri; Mohd Kassim, Muhamad Saufi (Springer, 2020)
Rainfall erosivity is one of the main factors of soil erosion that is expected to change as climate variables alter and impact soil conservation policies significantly. It is important to understand the potential trends in rainfall erosivity and its impacts on the environment, especially in tropical areas where severe rainfall is expected to continue to rise. This study aimed to project spatial and temporal rainfall erosivity factor using ensemble Global Circulation Models (GCMs). The study employed 20 GCMs, four RCPs scenarios, and two projection timescales (2050s and 2080s). The erosivity factor was determined by integrating baseline rainfall intensity with Modified Fournier Index (MFI). The values of erosivity were then interpolated using GIS software, and thematic maps were generated for these variables. The result shows 92% coefficient of determination between observed and simulated rainfalls. The ensemble model revealed that the MAE, SE and RMSE are 0.1487, 1.3692 and 1.2499, respectively. The relative increment of rainfall erosivity ranged from 4.7% to 122% with the highest value of 6292 MJmmha−1 hr−1 yr−1 by 2080s at Kg. Raja sub-basin located at North-Western part of the watershed. Similarly, the peak flow response through Ringlet river was expected to increase in the range of 4.72–35.8% with peak discharge in December by 2080s under RCP8.5 emission scenario. This study disclosed a potential increase in rainfall erosivity, and availability of water resources influenced by climate change which require appropriate conservation strategies.